Mobilization of human mesenchymal stem cells through different cytokines and growth factors after their immobilization by sulfur mustard. (1st September 2018) - Schreier, Cassandra; Rothmiller, Simone; Scherer, Michael A.; Rummel, Christoph; Steinritz, Dirk; Thiermann, Horst; Schmidt, Annette
Highlights: Even small concentrations of SM (from IC1 = 1 μM SM) resulted in a significant reduction of MSC migration activity. IL-8 (e and m) and IL-6 significantly compensated the SM induced migration reduction. The compensation of the SM-induced migration reduction by addition of cytokines could possibly solve the wound healing problems. Abstract: Introduction: The chemical warfare agent sulfur mustard (SM), also known as mustard gas, was first used in World War I. Although prohibited by the chemical warfare convention, significant amounts of SM still exist and have still to be regarded as a threat for military personnel and civilians. After SM exposure, the most prominent clinical symptom is the development of extensive non-healing skin wounds. This chronic wound healing dysfunction is persisting over long time. Mesenchymal stem cells (MSC) are known to play an important role in wound healing. Moreover, it is also known that patients with chronic wound healing diseases have compromised mesenchymal stem cell functionality. Based on these observations and the known relationship between wound healing dysfunction and MSC function we investigated the impact of sulfur mustard on human MSC. Material & methods: Mesenchymal stem cells (MSC) were isolated from femoral heads of healthy donors. They were cultured for less than four passages. MSC were exposed towards different sulfur mustard concentrations. After exposure we analyzed the secretome and the migration capacity. The migration capacity under influence of SM was analyzed after treatment with various cytokines. Results: SM exposure (even at very low concentrations) showed negative effects on the migration capability. Many cytokines that are necessary for MSC migration were secreted in a reduced manner. The reduced migratory capacity can be compensated in part by the addition of cytokines. Here especially IL-8 (e and m) and IL-6 significantly compensated the SM induced migration reduction. Discussion: The effect of sulfur mustard on MSC might play an important role in the persistence of long-term adverse effects; here the reduced migration could particularly be important. The compensation of the SM-induced migration reduction by addition of cytokines could possibly solve this problem. Moreover, our current results will help to understand the relationship between alkylating agents and MSC and thus will also give guidance in the future perspective for the therapeutic use of MSC in patients suffering from sulfur mustard induced chronic skin wounds.